Epidemiology of gastrointestinal parasitism in goats in Sikkim - RAHMAN, H; PAL, PAPRI; BANDYOPADHYAY, S; CHATLOD, L R (The Indian Journal of Animal Sciences, 2012)
An epidemiological study on gastrointestinal parasitic infection in goats in 4 agro-climatic zones of Sikkim during 2001 to 2010 was conducted. Out of 12 604 animals examined, 7933 (62.94%) were found to be positive for different gastrointestinal parasites either single or mixed infection with mean egg per gram of faeces (epg) 1364.68. The prevalence of different parasites was strongyles (46.72%), Strongyloides spp. (31.57%), Nematodirus spp. (17.01%), Eimeria spp. (19.4%), Moniezia spp. (9.89%),Trichuris spp. (3.95%), Toxocara spp.(2.55%), amphistomes (2.27%) and Dicrocoelium spp. (1.07%). The infection was more in subtropical high humid zone (70.48%) as compared to temperate humid zone (60.09%), sub-alpine low humid zone (23.81%) and alpine dry zone (7.56%). The faecal egg count of nematodes were ranged from 100 - 8400 with higher load during the rainy and post rainy seasons. The infection was higher in summer (74.71%) and autumn (73.62%) as compared to spring (63.08%) and winter (37.0%). The coproculture of positive samples revealed that order of prevalence of nematode infection were Haemonchus, Bunostomum, Oesophagostomum and Nematodirus spp. The gastrointestinal nematodes isolated from intestine during necropsy were Haemonchus contortus (64.91%) followed by Oesophagostomum columbianum (43.74%), Bunostomum trigonocephalum (35.63%), Nematodirus filicolis (15.76%), and Trichostrongylus colubriformes (8.28%). N. filicolis was reported for the first time in goats of Sikkim.